The Association of Muscle Dysmorphia, Social Physique Anxiety, and Body Checking Behavior in Male College Students With Weight Exercise - Zheng, Yu; Zhang, LiFeng; Shao, Ping; Guo, XueYing (Frontiers in Psychology, 2021)
Objectives: To investigate the association between muscle dysmorphia (MD), social physique anxiety, and body-checking behavior in male college students with weight exercise, and to reveal the association between them. Methods: A total of 492 male college students with weight exercise from 18 Fitness Clubs or bodybuilding centers in Chengdu, China, participated in this study. Results: First, the social physique anxiety scores, body checking frequency, and weight exercise behavior (i.e., frequency, time, and intensity) in male college students with MD were significantly higher than those without MD; it indicated that the higher the exercise frequency they had, the longer the exercise time they cost, and the higher exercise intensity carried out, and the higher the social physique anxiety scores tended to be, the higher the frequency of body checking on “global muscles,” “chest and shoulder muscles,” “comparison with others” and “posture measurement” they did. Second, the mediating effect of the social physique anxiety on MD and body checking was established in the "MD → global muscle checking," "MD → chest and shoulder muscle checking," "MD → comparison with others," and "muscle dysmorphia → posture measurement." Conclusion: Male college students with MD not only have a higher social physique anxiety, but also a higher frequency of body-checking behavior than the ordinary individuals. Social physique anxiety is one of the important mediating factors to those with MD which affects the body-checking behavior.